Comparison between Flipped Classroom Model and Traditional Lectures in Undergraduate Pediatric Students in terms of Knowledge Retention: - Tarar, Saba Haider; Iqbal, Javed (Medical Journal of South Punjab, 2024)
Objective: To make a Comparison between Flipped Classroom Model (FCM) and Traditional Lectures (TL) in Undergraduate Pediatric Students in terms of Knowledge Retention. Materials and Methods: It is an Interventional, quantitative Study with Post-positivism paradigm. It was carried out in Pediatrics students in MBBS, MC, Mirpur from April 01 to 30th September, 2022. Students were divided into 2 groups by randomization. Group A was given traditional lecture in the lecture hall for 2 weeks and group B received Flipped classroom instruction via audio recorded lectures and interactive sessions. Both groups were switched over after 02 weeks. At the end of 4 weeks, knowledge retention was assessed by marks obtained. Student’s perspective was assessed by a questionnaire. The data was analyzed in SPSS version 20. Results: The Pretest results of FCM group were higher as compared to TL group. The mean scores of pretest of FCM were 41.30%, 44.60%, 44.70% and 45.00% respectively. The post test scores of FCM group were significantly improved. The mean post test scores were 78.40%, 76.80%,76.50% and 76.30% respectively. The average increase in scores was 33.10 - 37.10%. The Pretest scores of TL group were significantly lower than FCM group. The mean pretest scores of TL group were 33.30%, 34.30%, 35.00% and 34.90% respectively. The mean post test scores were 64.10%, 68.10%, 69.20% and 67.77% respectively. The increase in scores was 27.90 - 34.80%. Regarding “FCM increases internal motivation” p-value was found to be significant (p-value 0.001) and FCM leads to better knowledge retention as compared to traditional lectures (p-value 0.002). Conclusion: FCM leads to significant improvement in knowledge retention.